Strategies for aquaculture and conservation of Neotropical catfishes based on the production of triploid Pimelodus maculatus - Bertolini, Rafaela Manchin [UNESP]; Lopez, Lucia Suarez [UNESP]; Nascimento, Nivaldo Ferreira do; Arashiro, Dilberto Ribeiro [UNESP]; Siqueira Silva, Diogenes Henrique de; Alves dos Santos, Silvio Carlos; Senhorini, Jose Augusto [UNESP]; Yasui, George Shigueki [UNESP] (Springer, 2020)
Triploidization is a technique to produce sterile fish on a large scale. In the spotted catfish Pimelodus maculatus, sterile fish serve as a host of germ cell transplantation for subsequent reconstitution of endangered catfish species. This study aimed to establish an efficient protocol for triploidization in P. maculatus using temperature shock. In this study, we tested the efficacy of heat shock treatments (37 degrees C, 38 degrees C, and 39 degrees C) applied at 2 min post-fertilization (mpf) for the duration of 2 min. Intact embryos served as diploid control. Ploidy status was confirmed by flow cytometry, characterization of erythrocytes nuclei, and karyotyping. Developmental stages were verified at cleavage, blastula, gastrula, somite, and hatching stages, as well as the percentages of normal and abnormal larvae. No significant difference was observed between the temperature treatments for percentage of unfertilized oocytes (P = 0.1834), 2-cell stage (P = 0.2348), blastula (P = 0.2972), hatching (P = 0.0668), and abnormal larvae (P = 0.6177). Heat shock decreased the survival at the blastula stage (P = 0.0178), somite (P = 0.0469), and the percentage of abnormal larvae (P = 0.0261). All treatments presented high percentages of triploid individuals, and the highest values were observed for heat shock at 38 degrees C (96.7 %). Based on the results described above, an efficient protocol for triploidization in P. maculatus was established using heat shock (38 degrees C) at 2 mpf for 2 min.
Keywords: Spotted catfish; Chimera; Chromosome manipulation; Polyploidy; Triploidization